Analysis of surgical bailout after transcatheter aortic valve replacement in Germany. (3rd October 2022) - Oettinger, V; Heidenreich, A; Kaier, K; Zehender, M; Bode, C; Duerschmied, D; Stachon, P; Von Zur Muehlen, C
Abstract: Background: Severe complications during transcatheter aortic valve replacement (TAVR) may require a surgical bailout. However, little is known about the outcomes after bailout in Germany. Methods: All TAVR between 2007 and 2020 were identified using German national electronic health records, with focus on 2018 to 2020. Additionally, those procedures requiring surgical bailout were selected. Results: A total of 159, 643 patients received TAVR. Overall rate of surgical bailout was 2.30% and overall in-hospital mortality 3.85%. In-hospital mortality after surgical bailout was 16.51%. While the annual number of procedures in all TAVR rose steeply (202 to 22, 972), the rate of surgical bailout dropped from 27.23 to 0.61% and that of overall mortality from 11.39 to 2.29%. However, mortality in case of surgical bailout remained high with 28.37% in 2020. After risk adjustment, in 2018 to 2020, standardized rates of overall in-hospital mortality and surgical bailout for both balloon-expandable and self-expanding transfemoral TAVR were significantly lower than for transapical TAVR (transapical vs transfemoral balloon-expandable vs self-expanding TAVR: in-hospital mortality: 5.66% [95% CI 4.81%; 6.52%] vs 2.30% [2.03%; 2.57%] vs 2.32% [2.07%; 2.57%]; surgical bailout: 2.33% [1.68%; 2.97%] vs 0.79% [0.60%; 0.98%] vs 0.42% [0.31%; 0.53%]). Main risk factors for surgical bailout were coronary artery disease (risk adjusted OR=1.50 [1.21; 1.85], p<0.001), atrial fibrillation (OR=1.29 [1.07; 1.57], p=0.009), and higher grade heart failure NYHA III/IV (OR=1.26 [1.01; 1.57], p=0.037). Conclusion: Rates of surgical bailout as well as overall in-hospital mortality after TAVR decrease substantially over the years. However, in the case of surgical bailout, outcomes remain poor with a constantly high in-hospital mortality. Funding Acknowledgement: Type of funding sources: None.